(untitled) (Journal of actual problems of jurisprudence, 2016)
This article is devoted to the development and definition of the concept of legal persons in the Republic of Kazakhstan.Legal entities are formed in many spheres of social and economic activity. Main legal form of the collective participation of individuals in public circulation and is the construction of a legal entity . When creating such organizations has created a complex set of relations, which require a special legal regulation by the state. Such regulation involves determining the legal status of the association, its symptoms, types of associations, their organizational – legal forms.